The Effects of Corporate Governance on Earnings Quality: Evidence from Iran - S. Bazaz, Mohammad; Mashayekhi, Bita (Asian Journal of Business and Accounting, 2010)
This paper seeks to examine the association between corporate governance mechanisms and the quality of accounting earnings. We intend to highlight the impact of a strong, religious-based, central government where certain attributes influence corporate governance. Specifically, the study empirically investigates whether the association of corporate governance mechanisms with earnings quality (in particular, accrual quality, earnings persistence, and earnings predictive ability) in Iran is different from what has been established in accounting literature for other countries. Among many corporate governance components, four (4) variables of board size, extent of independent directors, board leadership, and the frequency of the board meetings are considered in this paper. We test our hypothesis using a sample of six hundred (600) firm-year observations of the Tehran Stock Exchange from 2005 to 2008. The general findings are: a larger board size yields a weaker earnings quality; and an increase in the number of independent directors and frequency of the board meetings, strengthen the firm’s earnings quality in terms of earnings persistency and earnings predictability, however, they do not strengthen the accruals earnings. We, however, find no significant relationship between leadership structure and Iranian firms’ earnings quality.